Isolation of bacterial contaminants from elevator buttons of Faculty of Dentistry and Faculty of Allied Health Sciences in IIUM Kuantan - Azreel, Nur Fadhilah Hana; Alias, Norsyuhada (2018)
Background: Large buildings such as hospitals, universities, malls and health care centers tend to have elevators as the main transportation to connect people to places with substantial traffics almost every day. Elevator button surfaces in medical, educational and community settings may be regarded as under-recognized sites of bacterial contamination however recent studies have proven otherwise whereby high prevalence of bacterial colonization is observed. Frequently used public surfaces are the most common bacterial sources for infection transmission through direct or indirect contact with clothes and exposed skin such as fingertips. Through this study, isolated fungal and bacterial contaminants from the elevator button surfaces of dentistry and allied health sciences faculties were investigated, implementing awareness of importance of hand hygiene as well as disinfecting management of the elevator button surfaces in the community. Methods: The sampling procedure was derived from Mustafa et al., (2015) and was done in duplicate from the elevator buttons of the faculties to obtain the average number of colonies of the contaminants on nutrient agar ranging from low, medium and high contamination levels. The samples then were cultured on both selective and differential agars (MacConkey, mannitol salt and potato dextrose) followed by Gram staining for contaminants categorization and identification according to types and species. Results: Average number of colonies of isolated contaminants ranged from medium to high level of contamination. Most isolates identified were Gram-positive Staphylococcus aureus, followed by coagulase-negative Staphylococcus species and several Gram-negative bacteria. Conclusion: The study showed that elevator button surfaces could lead to transmission of potentially pathogenic bacteria. Significant importance of hand hygiene and disinfecting management of the elevator buttons should be applied to several locations with high potential contamination such as laboratories, clinics as well as toilets near to elevators.